الجريمة المعلوماتية ضد الطفولة جريمة تتحدى الواقع وتسابق التشريع. - بن لعامر, وليد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
مع تطور تكنولوجيا المعلومات وتعميم انتشار استخدام شبكة الانترنت الذي تزامن إلى حد ما مع ظهور مفهوم العولمة، ما ترتب عنها قيام العديد من الجرائم خاصة تلك التي تشكل تهديدا وخطرا على مصير الأطفال ومستقبلهم وهذا ما يبدو جليا من خلال الحجم الكبير لعدد الجرائم التي يكون فيه الأطفال هم الضحايا. ولقد اتجهت جهود الدول إلى حماية هذه الفئة الهشة بوضع مجموعة من الضوابط لحمايتها، من خلال التصدي للجريمة المعلوماتية بما يتماشى وقواعد مراعاة حرمة الطفولة في ظل التطور التكنولوجي وتسعى هذه الدراسة إلى معرفة خصوصية الجرائم الإلكترونية المرتكبة ضد الأطفال، والذي تراعي فيه الجزائر أهمية بالغية من أجل تقرير حماية قانونية لهذه الفئة الهشة في ظل التطور التكنولوجي والأثار السلبية التي تلحق بهم من خلال إقرار جملة من النصوص المجرمة للجريمة الإلكترونية عموما، والوقوف على الأحكام التي جاءت بها الاتفاقيات الدولية التي تراعي حماية حقوق الطفل داخل الشبكة المعلوماتية ومحاولة التصدي لها بالطرق القانونية. With the development of information technology and the widespread use of the Internet, which coincided to some extent with the emergence of the concept of globalization, what resulted in many crimes, especially those that pose a threat and danger to the fate of children and their future, and this is evident through the large number of crimes in which children are They are the victims. The efforts of states have tended to protect this vulnerable group by setting a set of controls to protect them, by addressing information crime in line with the rules of child sanctity in light of technological development. This study seeks to know the specificity of cyber crimes committed against children, in which Algeria takes great importance in order to A legal protection report for this vulnerable group in light of the technological development and the negative effects that afflict them by adopting a number of criminal texts for cybercrime in general, and standing on the provisions of international agreements that take into account the protection of children's rights within the information network and trying to address them by legal means.